Strategy for Improving Service Quality of Fatour Travel Bureau PT. Padang Tourism Choices on the Satisfaction of Hajj and Umrah Pilgrims - Lowis Gunsoles (Yayasan Darussalam Bengkulu, 2023)
The more competitors there are in the Hajj and Umrah travel business and as the interest of prospective pilgrims increases in their interest in carrying out the Hajj and Umrah pilgrimage, the quality of service determines the services of the Padang Fatour Travel Office. Implementing a strategy to improve service quality is the key to pilgrim satisfaction and the success of a Hajj and Umrah travel agency in achieving competitiveness. Every company is required to be able to develop and implement a strategy to improve service quality, thereby resulting in satisfaction for Hajj and Umrah pilgrims. In running a business, the company's service quality must provide services that are by Islamic law, of course, the services provided are services that are approved by Allah SWT with the values of beauty in service and actions that are by what Allah SWT permits and prohibits in carrying out activities. economy. The method used in this research is a qualitative approach, which is a field survey and is descriptive. The data collection methods used by the author in this research are observation, documentation, and interviews. The research results show that the strategy to improve service quality carried out by the Fatour Travel Office on the satisfaction of Hajj and Umrah pilgrims is the first strategy, the Fatour Travel Office must maximize branch offices by utilizing social media as a promotional tool. Second, forming an alumni organization to attract prospective pilgrims and so that congregations return to be loyal or subscribe to the services of the Fatour Travel office. Third, the Fatour Travel Office must create a new program, namely creating weekly ritual activities at least once a week. Because ritual activities are important or core activities when pilgrims before leaving for the holy land carry out the Hajj and Umrah.